Patients' outcomes related to person-centred nursing care in radiation oncology: A case study. Issue 6 (December 2015) - Rose, Pauline; Yates, Patsy
Abstract: Purpose: The aim of this case study is to describe patients' responses to nursing care following the implementation of a person-centred model in a radiation oncology department. Method: An instrumental case study design utilised surveys to collect data on a range of key patient outcomes: patient satisfaction (PSS), informational issues (RSEP), quality of life (FACT_G), comfort (RTCQ), and emotional status (HADS). This occurred at the beginning of, and twelve months following, the implementation of the new model of care. Results: This study demonstrated that, although adverse effects of radiotherapy continue to affect patient well-being in the latter part of their course of radiation therapy, patients continue to be satisfied with nursing care. There were significant differences between groups in perceptions of the care environment and the use of the nurse as an acknowledged source of information are noteworthy, since these variables were key targets of the new model of care. The finding that nurses were seen by the post-implementation cohort as more likely to be a source of information is an important indicator that the nurses' presence was noted by patients, and they generally reported high levels of functioning despite undergoing a curative course of radiotherapy. Conclusion: The person-centred nursing approach in the radiotherapy setting has contributed to some improvements in the provision of patient care. Aspects of this study may assist in planning further nursing interventions for patients undergoing radiotherapy for cancer, and continue to enhance the contribution of the radiation oncology nurse to improved patient outcomes. Highlights: Nurses provide supportive care for patients undergoing radiation therapy. Nurses have a role in information provision for patients. Nurses may contribute to providing a comfort environment for patients and their families. Person-centred nursing care may be an important approach to care in the radiation oncology setting. Person-centred nursing care may improve aspects of patient outcomes in the radiation oncology setting.